EDUCATIONAL VALUES’ ANALYSIS RELATED TO KHD’S PRINCIPLE IN THE RON CLARK STORY MOVIE - Anisa Mafiroh; Hazairin Eko Prasetyo (JELLT (Journal of English Language and Language Teaching), 2017)
The Ron Clark Story movie belongs to the American TV movie that is very interesting to watch. It tells about an energetic, creative, and idealistic young teacher who is able to encourage his students to reach their full potential learning. As a future teacher, the researcher was interested to do this qualitative research in order to find out the themes of the story, the educational values and the educational values related to Sistem Among that are drawn from the movie. The researcher used document review and literary study as the data collection techniques. Meanwhile, qualitative analysis was used as the data analysis technique. The result of this study showed that the themes of the story were social and personal themes. The educational values were hard work, love, positive attitudes, and gratitude. Finally, the educational values related to Sistem Among were drawn through the familial relationship, individual freedom, and natural law.